Prophylactic Use of Meloxicam and Paracetamol in Peripartal Sows Suffering From Postpartum Dysgalactia Syndrome - Schoos, Alexandra; Chantziaras, Ilias; Vandenabeele, Jordy; Biebaut, Evelien; Meyer, Evelyne; Cools, An; Devreese, Mathias; Maes, Dominiek (Frontiers in Veterinary Science, 2020)
Postpartum dysgalactia syndrome (PPDS) is a major economic problem in modern sow farms. General treatment of PPDS consists of the use of oxytocin to promote milk ejection and non-steroidal anti-inflammatory drugs (NSAIDs) to alleviate inflammatory processes. So far, studies investigated the use of a single administration of NSAIDs after parturition in healthy and non-healthy sows. The current study investigated whether administration of meloxicam or paracetamol in sows prior to parturition improves sow and piglet health as well as performance in a farm with PPDS problems in sows. Sixty sows and 978 piglets from a Belgian farrow-to-finish farm were enrolled. Sows were randomly divided into three groups: a non-treated control group, a meloxicam-treated group and a paracetamol-treated group. Treatment was administered orally for 7 days from gestation day 113 onwards. Performance and health parameters investigated in sows were gestation length, farrowing duration, litter characteristics, colostrum yield and quality (Immunoglobulin G), litter weight gain, weaning-to-estrus interval, pregnancy rate, rectal temperature, acute phase proteins and inflammatory markers serum amyloid A, haptoglobin, interferon γ, interleukin 1β and 6 backfat, constipation and feed refusal. Performance and health parameters in piglets were birthweight, average daily weight gain, colostrum intake and mortality. Paracetamol-treated sows showed a significantly (P = 0.04) lower rectal temperature (mean ± SD: 38.09 ± 0.18°C) than the meloxicam-treated sows (38.24 ± 0.18°C), but not than the control group (38.22 ± 0.18°C). Sows of the paracetamol-treated group had a significantly (P = 0.001) longer gestation length (116.3 ± 0.9 days) than sows of the control group (115.3 ± 0.6 days), but not than meloxicam-treated sows (115.9 ± 0.9 days). No significant differences between the three groups were found for all the other parameters. In conclusion, the prophylactic oral administration of either meloxicam or paracetamol for 7 days starting 2 days prior to farrowing did not show beneficial effects on both health and performance parameters of sows and piglets.